MECHANICAL CHARACTERISTICS OF POLYMERS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Polymers are a unique group of materials with many useful properties at a low cost. Despite the fact that plastics entered people's lives quite recently - less than a century ago - today it is absolutely impossible to imagine life without polymers.